Vegetation change on mountaintops in northern Sweden : Stable vascular-plant but reordering of lichen and bryophyte communities - Hagenberg, Liyenne Wu Chen; Vanneste, Thomas; Opedal, Øystein Hjorthol; Petlund, Hanne Torsdatter; Björkman, Mats Peter; Björk, Robert G.; Holien, Håkon; Limpens, Juul; Molau, Ulf; Graae, Bente Jessen; De Frenne, Pieter (Ecological Research, 2022)
publishedVersion